2010
DOI: 10.1016/j.neuroimage.2009.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Family history of alcoholism mediates the frontal response to alcoholic drink odors and alcohol in at-risk drinkers

Abstract: Although a family history of alcoholism is the strongest risk factor for developing alcohol dependence, there are few studies of the association between familial alcoholism and the human brain's reward system activity. We used functional magnetic resonance imaging (fMRI) to determine how family history affects the brain's response to subjects' preferred alcoholic drink odors (AO) as compared to appetitive control odors (ApCO). Fourteen non-dependent heavy drinkers (HD) who were family history positive (FHP) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 78 publications
7
95
1
Order By: Relevance
“…If alcohol consumption is at least partially mediated by palatability, the release of endogenous MOR ligands would be expected to promote further consumption. In keeping with this hypothesis, recent data indicate that an alcohol infusion, which bypasses gustatory mechanisms, does not alter blood oxygen leveldependent (BOLD) signal in the OFC of either subjects with a family history of alcoholism or matched controls (13). Although our data are consistent with the idea that drinking alcohol induces endogenous opioid release in the OFC, our study cannot distinguish between the contributions of the characteristic taste and smell of alcohol and a direct action of alcohol on the brain.…”
Section: Discussionmentioning
confidence: 90%
“…If alcohol consumption is at least partially mediated by palatability, the release of endogenous MOR ligands would be expected to promote further consumption. In keeping with this hypothesis, recent data indicate that an alcohol infusion, which bypasses gustatory mechanisms, does not alter blood oxygen leveldependent (BOLD) signal in the OFC of either subjects with a family history of alcoholism or matched controls (13). Although our data are consistent with the idea that drinking alcohol induces endogenous opioid release in the OFC, our study cannot distinguish between the contributions of the characteristic taste and smell of alcohol and a direct action of alcohol on the brain.…”
Section: Discussionmentioning
confidence: 90%
“…In that context, FHP subjects had the most robust VST DA release, which is consistent with other human imaging studies in which familial alcoholism modulates brain activation to alcohol cues. For instance, we (Kareken et al, 2010) and others (Tapert et al, 2003) have demonstrated that alcoholassociated cues differentially activate the medial prefrontal cortex (which sends axonal projections to the VST; for review see Haber and Knutson, 2010) as a function of FH. In contrast, an fMRI study of children of alcoholics did not detect a difference in VST activation for monetary rewards (Bjork et al, 2008), while another study of FHP subjects found reduced VST activation to monetary rewards compared with FHN subjects (Andrews et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, Weiss et al, 1993 found that rats selectively bred for high alcohol drinking showed a larger ventral striatal DA response to alcohol taste and intoxication than nonselected rats, suggesting that the genetic propensity for alcohol use disorders (AUD) is linked to differential striatal DA function. Two human studies found that, in subjects with a family history (FH) of alcoholism, the medial prefrontal cortex (which sends axonal projections to the striatum; Haber and Knutson, 2010), is activated more strongly in response to alcohol cues relative to family history-negative controls (Tapert et al, 2003;Kareken et al, 2010). Cue-elicited DA transmission may also relate to alcohol preference, as nonselected rats with the highest ethanol preference showed the largest increase in ventral striatal DA release in response to oral contact with alcohol (Doyon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ventromedial and medial prefrontal cortices are regions where neuronal activity varies as a function of the perceived reward value of stimuli (Hare, et al, 2009; Hare et al, 2008; Kable & Glimcher, 2007). Our laboratory has accordingly demonstrated that both alcoholic drink (Bragulat et al, 2008; Kareken et al, 2010a; Kareken et al, 2010b) and food aromas (Bragulat et al, 2010) robustly activate these medial frontal regions.…”
Section: Introductionmentioning
confidence: 97%